Research on Pressure bearing capacity of Defective Urban Gas Polyethylene Pipes. Issue 1 (March 2021) - Hai-zhou, Lv; Ming, Sun; Yu-bin, Xu; Yun, Wu; Long-long, Sun
Abstract: Polyethylene pipes have been widely used in the urban gas industry. However, there are few researches on the safety performance evaluation of polyethylene pipes in use at home and abroad, which makes it impossible to carry out Fitness-For-Service evaluation of defects found in the inspection, and thus cannot accurately judge the safety status of defective polyethylene pipes. In this paper, two typical polyethylene pipe materials, PE80 and PE100 are selected. Based on the tensile performance test, the constitutive model is established. Using the method of finite element simulation, the ultimate pressure bearing capacity of 9 defect models was analyzed and studied. And the relationship between defect size and pressure bearing capacity was initially determined. Provides a foundation for subsequent engineering applications.